1999
DOI: 10.1038/sj.bjc.6690248
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of angiogenesis in human pancreatic cancer

Abstract: To evaluate whether angiogenic factors are of clinical relevance to actual human pancreatic cancers, we studied the intratumoral microvessel density (IMD), and PD-ECGF, VEGF protein expression in 40 pancreatic cancers using immunohistochemistry. We also investigated PD-ECGF and VEGF gene expression using reverse transcriptase-PCR (RT-PCR). Of the 40 pancreatic cancers studied, 30 carcinomas (75.0%) were evaluated to be PD-ECGF -positive and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
207
2
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(226 citation statements)
references
References 37 publications
5
207
2
12
Order By: Relevance
“…13 Although considered as an hypovascular tumor, angiogenesis is nonetheless critical for the development and growth of PDAC. 27 In patients with such neoplasia, VEGFA expression in the tumor and high serum concentration are significantly correlated to a decreased median survival time 37,38 and to metastasis progression, especially to the liver. 28 The correlation between VEGFA expression and the survival remains significant even after a surgery putatively considered as curative.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although considered as an hypovascular tumor, angiogenesis is nonetheless critical for the development and growth of PDAC. 27 In patients with such neoplasia, VEGFA expression in the tumor and high serum concentration are significantly correlated to a decreased median survival time 37,38 and to metastasis progression, especially to the liver. 28 The correlation between VEGFA expression and the survival remains significant even after a surgery putatively considered as curative.…”
Section: Discussionmentioning
confidence: 99%
“…32 The angiogenic properties of pancreatic cancer remain unclear, partially because pancreatic cancers have been considered hypovascular, based on roentgenographic findings. However, it has been shown that tumor angiogenesis is implicated in the rapid growth and metastasis of pancreatic cancer, 33 and some angiogenesis inhibitors efficiently inhibited tumor growth and metastasis of pancreatic cancer in experimental models. 34 -36 It was recently reported that NK4 is an angiogenesis inhibitor, which not only antagonizes HGFinduced angiogenesis but also abrogates the angiogenesis induced by other angiogenic inducers such as bFGF and vascular endothelial growth factor, and its antiangiogenic activity is likely to be exhibited through mechanisms distinct from its HGF -antagonist activity.…”
Section: Discussionmentioning
confidence: 99%
“…12,30 Consequently, a variety of different inhibitors of VEGF activity have been developed, including humanized neutralizing anti-VEGF monoclonal antibodies, 31 soluble VEGF-Rs, 32 anti-sense VEGF mRNA expressing constructs, 33 VEGF-toxin conjugates, 34 and inhibitors of VEGF-R function. 35 Because VEGF is implicated in the angiogenesis of human pancreatic cancer 15,19,36 and VEGF expression has been shown to be associated with a poor prognosis in human pancreatic cancer, [37][38][39] we investigated the efficacy of a VEGF-R2 antibody, DC101, with or without gemcitabine on primary tumor growth and metastasis of human pancreatic cancers growing orthotopically in nude mice. Treatment with gemcitabine or DC101 alone resulted in an ϳ65% and ϳ70% reduction of primary pancreatic tumor volume, respectively, as compared to control.…”
Section: Analysis Of Tissue Hypoxiamentioning
confidence: 99%